Evaluation of a Heuristical Algorithm for Transit Line Planning - Juraj Cenek (Communications - Scientific letters of the University of Zilina, 2013)
Transit line routing is apart of strategic planning of transportation services in aregion. As such it is vital for providing services of astandard quality for an acceptable price. From a mathematical point of view line planning is an NP hard problem which is difficult to solve and so mostly heuristic methods or an interactive approach supported by simulations are used. The paper describes shortly a new heuristic algorithm, evaluates its quality on a design of set of regional lines and compares the designed plan with a current transportation services in a real region chosen as an example.